A Normative Legal Analysis of the Alleged Pertamax-Pertalite Fuel Adulteration: Corporate Criminal Liability and Consumer Protection Perspectives - Salsabila Nada Khansa; Aries Isnandar (Ius Poenale, 2026)
This study examines the alleged mixing of Pertalite into Pertamax from the perspectives of Indonesian criminal law, corporate criminal liability, and consumer protection. Using a normative juridical method, it analyzes statutory regulations, legal doctrines, court decisions, and relevant literature through statutory and conceptual approaches. The study finds that fuel adulteration may satisfy the legal elements of fraud where there is a discrepancy between the fuel quality represented to consumers and the product actually distributed. Such conduct may also give rise to corporate criminal liability under the National Criminal Code and consumer protection obligations under Law Number 8 of 1999 on Consumer Protection, including potential compensation through individual or collective claims. The study concludes that accountability for fuel adulteration requires an integrated application of criminal law, consumer protection law, and energy-sector regulation, supported by stronger regulatory oversight, transparency, and effective enforcement mechanisms..